China’s Interaction with the Outside World under the Conditions of the “New Normality” of the Chinese Economy - N. N. Kotlyarov (Мир новой экономики, 2018)
In recent years, the concept of “new normality” has been widely used in China, which was developed in the context of slowing the dynamics of the country’s economic development in the previous years. The concept is based on the premise that a slowdown in economic growth is a natural process, conditioned by objective reasons, and the existing growth indicators will continue in the foreseeable future. At the same time, it is stressed that China’s economic development is much faster than in other countries, and the PRC has every opportunity to even strengthen its role as one of the main participants and locomotives of the world economy. In China, it is stressed that over the years of the reform policy, the size of the Chinese economy has grown significantly, the country has entered the second place after the US in terms of GDP in the world and the existing indicators are not low at all. At the same time, the “new normality” (xin changtai) presupposes the main emphasis in the work of the government not on accelerating the rates of economic growth, but on ensuring the qualitative development of the economy.